Concentration Monitoring of Plasma Ribavirin: Validation of a Liquid Chromatography-Mass Spectrometric Method and Clinical Sample Collection. Issue 1 (February 2016) - Brown, Nigel W.; Morgan, Phillip E.; Agarwal, Kosh; Tredger, John M.
Abstract : Background: A liquid chromatography-tandem mass spectrometric (LC-MS/MS) method was developed for routine measurement of ribavirin concentrations in EDTA-anticoagulated plasma. Methods: After protein precipitation, we used a bridged ethylene hybrid (hydrophilic interaction) chromatography column, 0.1 mmol/L ammonium formate pH 3.0, and a gradient of 85%–96% acetonitrile to achieve baseline separation of ribavirin from isobaric uridine. Quantitation was assured using both primary (m/z 245.3 > 113.0) and secondary transitions (m/z 245.3 > 96.0) of the protonated species. Chromatographic separation and column washing also negated interference from major phospholipid species. Results: There was a linear relationship between concentration and response to 10 mg/L, with a minimum detectable level and a minimum level of quantitation both of 0.1 mg/L. Imprecision within the assay was <10% at 0.1 mg/L and <6% between assays for concentrations >0.4 mg/L. Bias was <4%. In clinical samples (n = 12), there was no difference in ribavirin concentrations obtained by an established liquid chromatographic assay with ultraviolet detection. Ribavirin concentrations were stable in plasma stored at room temperature for 3 days but then decreased significantly on day 7. Plasma concentrations were stable for 15 weeks at −20°C. Concentrations in plasma separated from whole blood at room temperature fell by a median of 19.4% at 4 hours and then rose substantially (median 251% by 3 days). Dose-normalized ribavirin concentrations reached a steady state after a mean of >6 weeks treatment in 76 patients with hepatitis C. Conclusions: A hydrophilic interaction liquid chromatography-tandem mass spectrometric method to measure ribavirin in plasma was developed. Samples for ribavirin estimation should be kept at 4°C, separated within 2 hours of collection and stored at 4°C before analysis, with long-term storage at −20°C. This method was applied to a study of the ribavirin therapeutic monitoring in patients with hepatitis C.